(obligation of Top Management, training and participation of individuals workers, customer satisfaction, continuous improvement, Strategically planning) - Al-Jarjari, Khudair K.M. (Humanities Journal of University of Zakho, 2016)
The research inicatet to declare the most pillar of Total Quality Management which represented in (obligation of Top Management, training and participation of individuals workers, customer satisfaction, continuous improvement, Strategically planning), and their effects in improvement of organizationl performance in industrial organizations to provide a clear way in conformance the continuous difficulties because of speed changing in the world of businesses which is represented in the increasing of a sharp competition between the companies and the consequent need to provide the best products and service and the lowest prices so that the company can prove itself in this competitive market. A group of six industrial companies have been chosen to be the field in which the practical part would be done. The researcher has depended on the questionnaire as a main tool to collect the data and the information in the practical part of the study, to achieve the aims of the study and to test the hypotheses of the study, a hypothetical model has been designed to show the nature of the relationship between the variables in the study. Depending on the description and the specification of the variables in this study and testing the correlation relationships and the impact, a set of conclusions have been reached. The most prominent conclusions are there is a positive significant correlation relationship and significant impact relationship among the Total Quality Management Fundamentals and the improvement of organizations performance in all the examined companies. Depending on the conclusions that have been reached by the researcher, the study presents a number of suggestions, notably the need to adopt the Total Quality Management Fundamentals to enhance the achievement of the performance of enterprise of companies surveyed